Gold nanocages as contrast agents for spectroscopic optical coherence tomography - Cang, Hu; Sun, Tao; Li, Zhi-Yuan; Chen, Jingyi; Wiley, Benjamin J; Xia, Younan; Li, Xingde (Optics letters, 2005)
We describe gold nanocages as a new class of potential contrast agent for spectroscopic optical coherence tomography (OCT). Monodispersed gold nanocages of an approximately 35 nm edge length exhibit strong optical resonance, with the peak wavelength tunable in the near-infrared range. We characterized the optical properties of the nanocage by using OCT experiments along with numerical calculations, revealing an absorption cross section approximately 5 orders of magnitude larger than conventional dyes. Experiments with tissue phantoms demonstrated that the nanocages provide enhanced contrast for spectroscopic as well as conventional intensity-based OCT imaging.